Association Between Gastrointestinal-Related Quality of Life and Frailty Using Baseline Data of the Prospective Cohort Study (JUSTICE-TOKYO Study) - Daisuke Asaoka; Osamu Nomura; Koji Sugano; Kei Matsuno; Hiroyuki Inoshita; Nobuto Shibata; Hideki Sugiyama; Noemi Endo; Yoshiyuki Iwase; Miyuki Tajima; Naoko Sakuma; Megumi Inoue; et al. (Diagnostics)
Objective: To determine the prevalence of frailty and examine its association with gastrointestinal-related quality of life (QOL) among older outpatients in a geriatric hospital. Methods: This cross-sectional study involved 1042 outpatients (age: ≥65 years) diagnosed using the revised Japanese version of the cardiovascular health study criteria. Data collection was performed by a multidisciplinary team. Results: Of the 1039 eligible subjects (male: n = 460 [44.3%]; mean age: 78.2 ± 6.1 years), 172 (16.6%) had frailty (male: n = 77 [44.8%]; mean age: 80.9 ± 6.2 years). The multivariate analysis revealed that age (odds ratio [OR]: 1.070, p < 0.001), QOL (OR: 0.982, p = 0.009), a history of falls (OR: 1.702, p = 0.029), sarcopenia (OR: 4.708, p < 0.001), steroid use (OR: 3.741, p = 0.001), analgesic drug use (OR: 2.056, p = 0.014), Mini Mental State Examination (OR: 0.915, p = 0.011), Geriatric Depression Scale 15 (OR: 1.101, p = 0.008), fullness-related QOL score (OR: 1.119, p = 0.010), chronic obstructive pulmonary disease assessment test (OR: 1.048, p = 0.007), and 10-item Eating Assessment Tool (OR: 1.071, p = 0.009) were related to frailty. Conclusions: The prevalence rate of frailty in older outpatients at a university hospital specializing in geriatric medicine was higher than that previously reported in community-dwelling individuals. Our study clarified that the fullness-related QOL score was related to frailty.